Rewetting as a hot-moment for NO3- and NH4+ consumption in sediment of non-perennial rivers in the semiarid region - Velasquez-Vottelerd, Patricia A.; Silva, Antonio E. B.; Queiroz, Hermano M.; Pereira, Tamara M.; Nóbrega, Gabriel N.; Duarte, Maria R. N.; Oliveira, Daniel P.; Rezende, Carla F.; Ferreira, Tiago O. (Frontiers in Water, 2025)
Non-perennial rivers (NPRs) occur all over continents, despite more than 50% being located in arid, semi-arid, and tropical regions. NPRs act as biogeochemists hotspots, in which flows drive ecological processes and nutrient cycling (e.g., nitrogen – N). The aim of this study was to investigate how the hydrological regime drives nitrogen concentrations and forms in an NPR located in the semi-arid region of Ceará, Brazil. We hypothesized that the rewetting phase acts as a “hot moment” for nitrogen dynamics, resulting in N depletion followed by increased concentrations during dry periods. We analyzed the physicochemical characteristic, nitrogen forms, organic carbon and sulfur concentrations of sediment samples (129) collected during three hydrological phases (Dry, Rewetting, and Flow). Physicochemical analyses indicated that the sediments were predominantly sandy and exhibited variations in redox potential (Eh), pH, and dissolved oxygen (DO). Regards the hydrological phases, amonium levels (N–NH4+) in sediments differed significantly across them, reaching values approximately four times higher (~74.9% increase) during the dry phase compared with the rewetting phase (i.e., dry: 3.25 ± 2.9 mg kg−1; flow: 2.49 ± 1.91 mg kg−1; rewetting: 0.72 ± 1.21 mg kg−1). For N-NO3-, concentrations in the dry and flow phases dry and flow phases were about 13 times higher than those observed in the rewetting phase, corresponding to 92.1% increase (i.e., dry: 1.34 ± 1.40 mg kg−1; flow: 0.85 ± 1.30 mg kg−1; rewetting: 0.12 ± 0.14 mg kg−1). Our results highlight the role of hydrological dynamics in influencing nutrient availability, suggesting that the rewetting phase should be considered a “hot moment” in NPRs. During this period, there is a rapid response in nitrogen processing driven by the water in the riverbed, which provides information on how drought could act on nutrient cycling. Such as most rivers in semiarid regions are non-perennial, prolonged droughts under climate change scenarios are expected to reduce primary production, impacting biodiversity (i.e., population and community ecology). This is particularly relevant in the context of reduced natural flow due to water abstraction, damming, and climate change.